The establishment of murine Hox-1 expression domains during patterning of the limb - Haack, H; Gruss, P (Developmental biology, 1993)
Region-specific expression patterns have been described recently for several candidate, developmental regulatory genes in the vertebrate limb. We have identified and mapped homeobox containing genes of the 5' part of the murine Hox-1 cluster by chromosomal walking. The expression of Hox-1.8, Hox-1.9, Hox-1.10, and a paralog of the Hox-4 cluster (Hox-4.5) were analyzed during stages when the developing limb pattern was being laid down. Each of these Hox genes was expressed in a restricted domain along the proximodistal axis of the limb at stage E 12.5. Only minor asymmetries were seen along the other two axes. A detailed spatiotemporal analysis of Hox expression, including three-dimensional reconstructions, revealed that the expression domains became progressively established between stages E 9.5 and E 12.5. Expression started from a small posterior and distal region and expanded toward the anterior part of the limb for 2 days. Depending on the gene and developmental stage, expression expands either along the ventral or the dorsal periphery. The establishment of the patterns was correlated to the growth process in the limb. Hox-1.8 and Hox-1.9 were also expressed in part of the somatopleure adjacent to the forelimb. The displacement of this domain toward the tip of the limb during development suggests that Hox-1.8 and Hox-1.9 were expressed in muscle precursor cells which migrate into the limb. The importance of these findings for the proposed models of limb pattern formation is discussed.